XRF maps of Paracas textiles and threads - Hacke, Marei; Javér, Anna; Thuresson, Kaj (Swedish National Heritage Board, 2021)
XRF dataset used in two publications:

Javér, A., M. Hacke, C. Thays Delgado, and K. Thuresson. 2017. Paracas textiles – Colour and condition. Investigation of the mordants and state of degradation of the Paracas textile collections in Peru and Sweden. In ICOM-CC 18th Triennial Conference Preprints, Copenhagen, 4–8 September 2017, ed. J. Bridgland, art. 1804. Paris: International Council of Museums.

and

Sabatini, F., Bacigalupo, M., Degano, I. et al. Revealing the organic dye and mordant composition of Paracas textiles by a combined analytical approach. Herit Sci 8, 122 (2020). https://doi.org/10.1186/s40494-020-00461-5
Keywords: XRF; Paracas; textile; 3.5.1-01504-2017; 3.5.1-00106-2016; 3.5.1-03996-2017; History and Archaeology; Historia och arkeologi